A systematic review of graduate training on cultural competence (Journal of Applied Learning and Teaching, 2023)
A systematic review was conducted to investigate scholarship from the last ten years regarding graduate training for the provision of culturally competent mental health care to individuals who hold marginalized identities (e.g., those marginalized based on their race, ethnicity, gender, sexual orientation). This review furthered a conceptualization of cultural competence that views clients as individuals embedded within their own cultures and communities while also recognizing the interplay of systems of power and oppression within an individual’s life that create unique lived experiences. This was accomplished by conducting a systematic literature review following PRISMA guidelines. Seven databases (i.e., PsycINFO [EBSCO], PubMed, Psychology and Behavioral Sciences Collection [EBSCO], Academic Search Complete [EBSCO], SocIndex [EBSCO], Science Direct, ProQuest) were searched using a priori-defined search strings that encompass graduate training, cultural competence, and the various mental health care fields. Recommendations for improving cultural competence conceptualizations, engendering innovative training interventions, and increasing rigorous evaluation tools are provided.